1998
DOI: 10.1099/00207713-48-3-859
|View full text |Cite
|
Sign up to set email alerts
|

Delimiting the genus Staphylococcus through description of Macrococcus caseolyticus gen. nov., comb. nov. and Macrococcus equipercicus sp. nov., Macrococcus bovicus sp. nov. and Macrococcus carouselicus sp. nov.

Abstract: Delimiting the genus. nov., are described on the basis of a phylogenetic analysis comparing 165 rRNA sequences, DNA-DNA liquid hybridization, DNA base composition, normalized ribotype patterns, macrorestriction pattern analysis and estimation of genome size using PFGE, cell wall composition, phenotypic characteristics and plasmid profiles. Compared with their closest relatives, members of the genus Staphylococcus, these organisms demonstrated significantly lower 165 rRNA sequence similarities (934-9503 %), hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
1
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(66 citation statements)
references
References 10 publications
2
61
1
2
Order By: Relevance
“…1A, lane 15). These results agree with the new taxonomic situation of S. caseolyticus, which has recently been reclassified as Macrococcus caseolyticus (19).…”
supporting
confidence: 82%
“…1A, lane 15). These results agree with the new taxonomic situation of S. caseolyticus, which has recently been reclassified as Macrococcus caseolyticus (19).…”
supporting
confidence: 82%
“…This analysis revealed that all the strains studied produce a single band of SOD activity ( Fig. 1 and data not (13). A single amplification product having the expected size of 480 bp was observed with all staphylococcal species (data not shown).…”
Section: Resultsmentioning
confidence: 98%
“…The 16S rDNA sequence-derived trees (40,41) gave different results, however, with 12 genogroups being identified. In fact, it has been shown that S. caseolyticus should be reclassified as Macrococcus caseolyticus (20), thus limiting the number of 16S rDNA gene sequence-derived genogroups.…”
Section: Discussionmentioning
confidence: 99%
“…The position of the organism should be regarded as uncertain, however, as low bootstrap values (Յ50%) were obtained in studies of the bacteria using 16S rDNA (41) and hsp60 (20) sequence data. The rpoB-derived data indicating that S. cohnii is outside the S. saprophyticus group and closely related to S. aureus are in disagreement with previously published data and may be incorrect.…”
Section: Discussionmentioning
confidence: 99%